Towards a personalized assessment of pancreatic function in diabetes. Issue 5 (3rd September 2017) - Sheu, Carey; Paramithiotis, Eustache
ABSTRACT: Introduction : Type 2 diabetes (T2D) is a complex progressive disease that poses significant challenges to delivery of individualized patient-centered care. Despite tremendous efforts, the critical need for biomarkers which accurately predict or monitor disease in individuals beyond classical risk factors has not been realized in the clinic. Given the underlying role of pancreatic dysfunction to disease etiology, this review aims to survey the literature to evaluate the utility of the available biomarkers for a personalized assessment of pancreatic islet function in diabetes. Areas covered : Literature survey and synopsis of genetic markers of monogenic and polygenic diabetes, imaging biomarkers, plasma metabolite and protein biomarkers, and multi-biomarker algorithms, in the context of personalized medicine. Arguments supporting the premise that the islet secretome is a logical place for discovery of the putative biomarkers with the required performance, supplemented with preliminary data for illustration purposes. Discussion of factors needed for successful adoption of biomarkers in the clinic. Expert commentary : Speculation on what delivery of personalized medicine in diabetes could entail, with the expectation that it will be predicated on the discovery of easy-to-deploy biomarkers specifically reflective of pancreatic islet health, used in combination with traditional risk factors.